2014
DOI: 10.1128/aem.00762-14
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lactobacillus plantarum CCFM8610 against Chronic Cadmium Toxicity in Mice Indicate Routes of Protection besides Intestinal Sequestration

Abstract: cOur previous study confirmed the ability of Lactobacillus plantarum CCFM8610 to protect against acute cadmium (Cd) toxicity in mice. This study was designed to evaluate the protective effects of CCFM8610 against chronic Cd toxicity in mice and to gain insights into the protection mode of this strain. Experimental mice were divided into two groups and exposed to Cd for 8 weeks via drinking water or intraperitoneal injection. Both groups were further divided into four subgroups, control, Cd only, CCFM8610 only,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 37 publications
(44 reference statements)
10
72
0
1
Order By: Relevance
“…Our previous study confirmed the ability of a probiotic, L. plantarum CCFM8610, to inhibit Cd absorption in the intestines of mice, and the protective mechanism is partly due to the intestinal sequestration by the Cd-binding ability of the strain (15,16). This study was performed to evaluate whether probiotics can inhibit Cd absorption through other routes besides Cd binding, with a focus on protection of the gut barrier.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Our previous study confirmed the ability of a probiotic, L. plantarum CCFM8610, to inhibit Cd absorption in the intestines of mice, and the protective mechanism is partly due to the intestinal sequestration by the Cd-binding ability of the strain (15,16). This study was performed to evaluate whether probiotics can inhibit Cd absorption through other routes besides Cd binding, with a focus on protection of the gut barrier.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, other studies have demonstrated that probiotics can protect against intestinal barrier disruption and decrease intestinal permeability by alleviating oxidative stress in animals (49,50). It has been confirmed that L. plantarum CCFM8610 exhibits good antioxidative ability in vitro and in vivo (14,15). Such an ability may protect it from the chain effects triggered by Cd-induced oxidative stress in the intestines.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Long-term exposure to Cd 2+ causes a variety of pathological conditions and poisons many cell types, including kidney, liver, brain, testis, lung, and thymus, both in vitro and in vivo [46]. Cd 2+ compounds promote tumorigenesis in the testes, lungs, and prostate as well as hematopoietic malignancies [7]. They also morphologically transform and induce chromosomal aberrations and gene mutations in cultured mammalian cells [8].…”
Section: Introductionmentioning
confidence: 99%